Aerodynamic Drag Reduction for a Generic Truck Using Geometrically Optimized Rear Cabin Bumps - Abdellah Ait Moussa; Justin Fischer; Rohan Yadav (Journal of Engineering)
The continuous surge in gas prices has raised major concerns about vehicle fuel efficiency, and drag reduction devices offer a promising strategy. In this paper, we investigate the mechanisms by which geometrically optimized bumps, placed on the rear end of the cabin roof of a generic truck, reduce aerodynamic drag. The incorporation of these devices requires proper choices of the size, location, and overall geometry. In the following analysis we identify these factors using a novel methodology. The numerical technique combines automatic modeling of the add-ons, computational fluid dynamics and optimization using orthogonal arrays, and probabilistic restarts. Numerical results showed reduction in aerodynamic drag between 6% and 10%.